A comparative study of preimplantation embryos development of young and aged mice treated with L-carnitine (Baghdad Science Journal, 2024)
Female aging is one of the main factors influencing reproductive fertility. The existing experimental study was planned to investigate the L-carnitine (LC) treatment effect on the body weight of adult young 8–10 weeks old and aged 26–28 weeks old female mice and the preimplantation embryonic development of their embryos. This study involved 40 mature young (n=20) and aged (n=20) old female mice. The animals were weighed and divided into 4 groups according to their age (n = 10).  The control groups of young and aged mice groups were orally administered distilled water, while the young and aged mice that were treated orally with 10 mg/kg LC daily for 2-3 estrous cycles were considered as treated groups. Then, all female mice were mated with adult males. The weight of pregnant mice on 1-day post coitum was recorded and then euthanized to harvest early cleavage embryos. The embryo development was examined and evaluated their grading according to A, B, C and D. The results showed that the body weight of mice in both young LC and aged LC groups reduced significantly (P≤0.01). The grade A embryo in 1-day post coitum in young and aged LC groups improved significantly (P≤0.01). However, the development of embryos grade A in the young LC group was higher than that of the aged LC group. It was concluded from these findings that the oral supplementation of LC can reduce body weight and improve the preimplantation embryonic development proportions.